The future of foreign investment in Southeast Asia - Freeman, Nick J.; Bartels, Frank L. (RoutledgeCurzon international business in Asia series ;, 2004)
This book portrays the dynamics that currently lie behind Southeast Asia's foreign investment activity, and seeks to identify the region's future options in reviving its reputation as an attractive host for foreign investors.